Preparation of biodiesel from waste cooking oil using single step batch catalyst with the aid of KOH as a catalyst - Najwa, Mohd Nor (2008)
Biodiesel is a cleaner burning diesel replacement fuel processed from natural, renewable derived from biological sources such as used vegetable oils and animal fats. The type of process that used to produce biodiesel is transesterification. Transesterification is the commonly process that used widely compare to other process. This process is important to convert free fatty acid (FFA) in oil to ester. In this research, waste cooking oil is used as raw material with Potassium hydroxide (KOH) as catalyst and methanol as a solvent. The reaction has been done in a water bath. The parameter that been investigated were reaction time and catalyst concentration while reaction temperature was fixed at 65˚C. Finally, the biodiesel sample was tested on several parameters which are the yield, thin layer chromatography (TLC), and moisture content.